Como crecen los perritos - Selsam, Millicent E. (Millicent Ellis), 1912-1996.; Bubley, Esther (New York : Scholastic, 1980)
Describes the first six weeks of six puppies' lives as they nurse, sleep, learn to walk, eat solid food, and interact with other dogs.
Translation of: How puppies grow.
Keywords: Puppies; Dogs